The Impact of Corporate Social Responsibility on Organizational Citizen Behavior in the Chinese Pharmaceutical Industry - LU, BINGQUAN (2017)
With the development of economy and society, the practice of corporate social responsibility has become an irreversible trend in the world. Many Western companies have raised corporate social responsibility to the height of the strategic management while enterprise in China has caused many social contradictions in the process of rapid development, which has been becoming a matter of concern for government, enterprise and scholar. Especially the Chinese pharmaceutical industry, its explosion recent 30 years while this promising industry frequently happen scandal because of lack of CSR consciousness .